Analysis of Readiness to Use Target Costing Method in Production Cost Efficiency Efforts at Risha Bakery - Yuliyanti Palulun; Dwi Iga Luhsasi; Destri Sambara Sitorus (Budapest International Research and Critics University, 2021)
Companies do not always have the ability to determine the selling price of the product as desired because there are a number of competitors offering a certain price. In order to maintain the quality of a product and have a competitive selling price, companies need to sort out the costs that are not needed in the production process so that profits can be more optimal. The target costing method is a method of determining the selling price based on market prices. Target costing aims to reduce production costs so as to optimize profit or profit. This study aims to analyze the readiness to use the target costing method at Risha Bakery. This type of research approach used in this research is a qualitative approach using descriptive analysis. The results showed that the readiness of Risha Bakery can be seen from several factors including setting the selling price as a means of competition with competitors, the desire of the company to get an increase in profit, setting cost targets, and reducing inefficient production costs or value engineering. Thus, Risha Bakery can be considered ready to use the target costing method.